Wacana Moderasi Beragama Kementerian Agama: Analisis Wacana Kritis Norman Fairclough: The Discourse of Religious Moderation by the Ministry of Religious Affairs: A Critical Discourse Analysis According to Norman Fairclough - Martalia, Martalia; Ashadi, Andri; Susilawati, Susilawati (Jurnal Sosiologi Agama Indonesia (JSAI), 2024)
This article aims to analyze the discourse of religious moderation as conveyed by the Ministry of Religious Affairs of the Republic of Indonesia, utilizing Norman Fairclough's critical discourse analysis (CDA) framework. The primary focus is on understanding how religious moderation is represented, how power relations are constructed, and how identity is formed through this discourse. The study adopts a qualitative approach, applying Fairclough's techniques for critical discourse analysis. Data were collected from content related to religious moderation on the official website of the Ministry of Religious Affairs of the Republic of Indonesia. The analysis divides the discourse into three levels: Microstructural, Mesostructural, and Macrostructural. At the Microstructural level, the findings indicate that the representation in the discourse of religious moderation includes comprehensive information and clear metaphors, establishing power relations and positioning journalists as part of governmental authority. At the Mesostructural level, it was found that the Ministry of Religious Affairs' website functions as a government information medium in the religious domain, with journalists as members of the Ministry of Religious Affairs, reaffirming power relations in the dissemination of the discourse. Furthermore, the Macrostructural analysis reveals that the Ministry of Religious Affairs' efforts to construct a narrative of religious moderation are a strategic response to social threats disrupting national unity, such as radicalism and intolerance. This study confirms that the Ministry of Religious Affairs of the Republic of Indonesia uses its website as the primary platform for spreading the discourse of religious moderation as an effort to face social challenges and strengthen national unity. The critical discourse analysis demonstrates that representation, power relations, and identity formation through the discourse of religious moderation play a crucial role in this effort. Abstrak Artikel ini bertujuan untuk menganalisis wacana moderasi beragama yang disampaikan oleh Kementerian Agama Republik Indonesia menggunakan kerangka analisis wacana kritis Norman Fairclough. Fokus utama adalah untuk memahami bagaimana moderasi beragama direpresentasikan, bagaimana relasi kuasa terkonstruksi, dan bagaimana identitas dibentuk melalui wacana tersebut. Kajian ini menggunakan pendekatan kualitatif, dengan menerapkan teknik analisis wacana kritis Norman Fairclough. Data dikumpulkan dari konten yang terkait dengan moderasi beragama pada situs web resmi Kementerian Agama Republik Indonesia. Analisis dilakukan dengan membagi wacana menjadi tiga tingkat yaitu Mikrostruktural, Mesostruktural dan Makrostruktural. Hasil kajian ini menunjukkan bahwa pada tingkat Mikrostruktural, representasi dalam wacana moderasi beragama mencakup informasi yang lengkap dan metafora yang jelas, membangun relasi kuasa dan memosisikan wartawan sebagai bagian dari otoritas pemerintah. Pada tingkat Mesostruktural, ditemukan bahwa situs web Kementerian Agama berfungsi sebagai medium informasi pemerintah dalam bidang keagamaan, dengan wartawan sebagai anggota dari Kementerian Agama, yang menegaskan kembali relasi kuasa dalam penyebaran wacana. Kemudian, analisis Makrostruktural menunjukkan bahwa upaya Kementerian Agama dalam membangun narasi moderasi beragama merupakan respons strategis terhadap ancaman sosial yang mengganggu persatuan bangsa, seperti radikalisme dan intoleransi. Kajian ini mengonfirmasi bahwa Kementerian Agama Republik Indonesia menggunakan situs webnya sebagai platform utama untuk menyebarkan wacana moderasi beragama sebagai upaya menghadapi tantangan sosial dan memperkuat persatuan nasional. Analisis wacana kritis menunjukkan bahwa representasi, relasi kuasa, dan pembentukan identitas melalui wacana moderasi beragama memainkan peran penting dalam upaya tersebut.